NILAI EKONOMI TANAMAN KEMIRI (Aleurites moluccana) PADA SISTEM AGROFORESTRI - Dian Puspaningrum (Agropolitan, 2018)
This study aimed to determine the economic value of candlenut planted by the community. The research method used in this research was the contribution value of the production of hazelnut plants using a simple economic formula while to calculate the biomass value and carbon value of the hazelnut plant using the allometric equation. The results showed that hazelnut seeds had the highest economic value amount Rp150.480.000/ year with the percentage was 70.6%. Then grain candle had an economic value of Rp61.950.000/ year with the percentage was 29%, and the lowest utilization of candlenut was hazelnut shell amount Rp930,000/ year with a percentage of 0.4%. Contribution from farming income was Rp213,360,000 with the percentage of 84%, bigger than the non-farm income amount Rp39.6 million with a percentage of 16%. The amount of biomass and carbon stocks in the Tapaluluo agroforestry candle plant yields a biomass were 0.0180 ton / ha and the carbon were 0.0084 ton / ha.